A proposed framework model for the online service quality of airline ticketing / Aida Wati Hashim - Hashim, Aida Wati (Faculty of Information Technology and Quantitative Science, 2005)
This research is proposing a framework on online service quality airline transportation. There are eleven dimensions of online service quality and electronic customer relationship management (E-CRM) used in a proposed framework. The objective of this research is to identify the favorable features of online service quality website by airline companies. Then, the second purpose is to propose a framework of service quality by airlines e-commerce website. The research began by designing a web evaluation form derived from literature reading and colleagues' discussion. 50 airline websites worldwide observe and evaluate at the end of October and finish by mid of November 2005. The airline website divided into categories; individual website and alliance website. The airline companies selected were those service ranked by Skytrax Airline Star Ranking Programme. The data that had been collected were analyzed using SPSS 11.0 and Microsoft Office Excel 2003. There are 28 favorable E-CRM features in airline website; account information, on-sale area, order, store locator, affinity program, account conditions, links, online purchasing, preview product, member benefits, posted privacy policy, membership, product information, company history/profile, postal address, e-mail, facsimile, site map, FAQs, product highlights, customization possibility, ability to track order status, mailing list, toll-free numbers, complaining ability, speed of download pages, and site customization. It is concludes that more than half out of 50 airline websites have 28 favorable E-CRM features.